2017
DOI: 10.1021/acs.chemmater.7b03212
|View full text |Cite
|
Sign up to set email alerts
|

Edge-On MoS2 Thin Films by Atomic Layer Deposition for Understanding the Interplay between the Active Area and Hydrogen Evolution Reaction

Abstract: The edge sites of molybdenum disulfide (MoS 2 ) have been shown to be efficient electrocatalysts for the hydrogen evolution reaction (HER). To utilize these structures, two main strategies have been proposed. The first strategy is to use amorphous structures, which should be beneficial in maximizing the area of the edge-site moieties of MoS 2 . However, these structures experience structural instability during HER. The other strategy is nanostructuring, in which, to enhance the resulting HER performance, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
115
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 57 publications
(84 reference statements)
9
115
0
Order By: Relevance
“…More interestingly, contrary to the traditional view that the number of edge sites is important, some studies also point out that the hopping efficiency of electrons in the vertical direction or the resistance plays a key role in the development of high-efficiency two-dimensional material catalysts [75][76][77]. Cao et al have investigated layer-dependent MoS 2 electrocatalytic activity by controlling the number of layers during the synthesis [76].…”
Section: Some New Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, contrary to the traditional view that the number of edge sites is important, some studies also point out that the hopping efficiency of electrons in the vertical direction or the resistance plays a key role in the development of high-efficiency two-dimensional material catalysts [75][76][77]. Cao et al have investigated layer-dependent MoS 2 electrocatalytic activity by controlling the number of layers during the synthesis [76].…”
Section: Some New Resultsmentioning
confidence: 99%
“…As the potential barriers exit in the interlayer gap, the electron transfer in the perpendicular direction is through hopping (Figure 9b), which makes the thicker sample shows poor electrocatalytic performance. Recently, Shin's group also investigated the electrocatalytic performance of MoS 2 with a different number of edge sites [77]. Their experimental results indicated that the thicker zone with the maximum number of edge sites did not exhibit the best HER performance, while the thin zone consisting of basal planes resulted in the best performance.…”
Section: Some New Resultsmentioning
confidence: 99%
“…It is imperative to develop a low‐cost hydrogen evolution reaction (HER) catalyst . Transition metals alloys and transition metals compounds, such as metal alloys, metal phosphide, metal nitride, metal carbide, and metal sulfide/fluoride with defect have shown their outstanding HER catalysis activity. Carbon materials such as heteroatom‐doped graphene, C 3 N 4 @N doped graphene and metal‐free covalent organic polymer (COPs) also showed excellent catalytic ability for hydrogen evolution reaction with easily prepared process.…”
Section: Introductionmentioning
confidence: 99%
“…atomic-layer deposition (ALD) and chemical vapour deposition (CVD). 12,15,17,[27][28][29][30][31] Synthetic MoS 2 films can be amorphous or crystalline with a texture of the crystalline material ranging from in-plane oriented grains (i.e. horizontally aligned layers) to complex 3D structures with out-of-plane oriented (OoPO) grains (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…15,17,27 It is well known that the differences in grain orientation of these highly anisotropic materials significantly impact film properties. 2,27,[31][32][33] Horizontally aligned grains are typically well suited for electronic applications, while OoPO grains are very efficient electrocatalysts. It is therefore of paramount importance to be able to characterize the texture of synthesized TMDs to optimize performance.…”
Section: Introductionmentioning
confidence: 99%